2015
DOI: 10.5847/wjem.j.1920-8642.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of children with acute poisoning: A three-year retrospective analysis

Abstract: BACKGROUND:There is a lack of evidence on description of burden and cases of childhood poisoning in developing countries. This study aimed to assess the characteristics of children with acute poisoning, and factors for time of presentation to health facility and nature of poisoning. METHODS:A cross-sectional study was conducted at three major pediatric referral hospitals in Addis Ababa, Ethiopia. Description of demographics of children with acute poisoning and factors associated with time to presentation and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
34
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 12 publications
(15 reference statements)
6
34
2
Order By: Relevance
“…Similarly, male preponderance is also seen in other studies, however one study in Ethiopia reported similar frequency in both boys and girls. 4,[6][7][8][9] Sixty percent of our study children are from the lower socioeconomic class which is similar to the findings by two other studies from Pakistan and Iran. 7,8 This is found to be statistically significant and is an important risk factor for accidental poisoning in children due to poor storage facilities in such households and along with poor supervision and parental neglect due to poverty and large family size.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Similarly, male preponderance is also seen in other studies, however one study in Ethiopia reported similar frequency in both boys and girls. 4,[6][7][8][9] Sixty percent of our study children are from the lower socioeconomic class which is similar to the findings by two other studies from Pakistan and Iran. 7,8 This is found to be statistically significant and is an important risk factor for accidental poisoning in children due to poor storage facilities in such households and along with poor supervision and parental neglect due to poverty and large family size.…”
Section: Discussionsupporting
confidence: 80%
“…This is in line to the reports by other authors like Bacha, Kohli and Farnaghi et al who reported 77.5%, 96.9% and 90% respectively. 4,6,8 Frequency of poisoning in children is more common among boys (72%) as compared with girls (28%) with a ratio of 2.57:1, which is statistically significant. Similarly, male preponderance is also seen in other studies, however one study in Ethiopia reported similar frequency in both boys and girls.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…33 The other studies reported drugs followed by kerosene are the most common poisoning agent in their study. [34][35][36] Out of 38 cases, 2 cases died. Both cases are of alluminium phosphide poisoning.…”
Section: Discussionmentioning
confidence: 99%